2013
DOI: 10.1136/bmjopen-2013-003154
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacist intervention for glycaemic control in the community (the RxING study)

Abstract: ObjectiveTo determine the effect of a community pharmacist prescribing intervention on glycaemic control in patients with poorly controlled type 2 diabetes.DesignPragmatic, before–after design.Setting12 community pharmacies in Alberta, Canada.ParticipantsType 2 diabetes receiving oral hypoglycaemic medications and with glycated haemoglobin (HbA1c) of 7.5–11%.InterventionPharmacists systematically identified potential candidates by inviting patients with type 2 diabetes to test their HbA1c using validated point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 14 publications
1
92
0
1
Order By: Relevance
“…Indicated that, a good control in blood glucose and lipid levels in patients with diabetes were seen in the pharmacist-run program. 42 The first completed study of independent prescribing by pharmacists conducted by Al Hamarneh et al, (2013) showed similar improvements with above studies in glycaemic control. The value of HbA1c was reduced and above 50% of the patients were achieved the target (≤7%), which represents pharmacist prescribing intervention in patients with poorly controlled diabetes clinically important in glycemic control.…”
Section: Effect On Glycated Hemoglobin A1c (Hba1c) Bp and Lipid Profmentioning
confidence: 56%
See 1 more Smart Citation
“…Indicated that, a good control in blood glucose and lipid levels in patients with diabetes were seen in the pharmacist-run program. 42 The first completed study of independent prescribing by pharmacists conducted by Al Hamarneh et al, (2013) showed similar improvements with above studies in glycaemic control. The value of HbA1c was reduced and above 50% of the patients were achieved the target (≤7%), which represents pharmacist prescribing intervention in patients with poorly controlled diabetes clinically important in glycemic control.…”
Section: Effect On Glycated Hemoglobin A1c (Hba1c) Bp and Lipid Profmentioning
confidence: 56%
“…The value of HbA1c was reduced and above 50% of the patients were achieved the target (≤7%), which represents pharmacist prescribing intervention in patients with poorly controlled diabetes clinically important in glycemic control. 53 Another cohort study was conducted with 126 patients to assess the impact of a pharmacist-managed insulin titration program compared to standard medical care on deprived glycemic control. The pharmacist-run group showed a better improvement in A1c outcome, compared to the standard care.…”
Section: Effect On Glycated Hemoglobin A1c (Hba1c) Bp and Lipid Profmentioning
confidence: 99%
“…Seven studies showed benefit in clinical patient outcomes. These studies found improved risk factor control in patients with prior stroke, 25 reduced systolic blood pressure 26,31 and low-density lipoprotein cholesterol, 27 improved glycemic control in patients with poorly controlled type 2 diabetes 22 and improved quality of life in patients with uncontrolled type 2 diabetes in a cost-effective manner. 32 Better chronic disease management as well as significant symptomatic improvement was reported by 81% of patients when pharmacists prescribed CLInICAL RevIeW medications for minor ailments (i.e., ambulatory conditions) in Saskatchewan.…”
Section: Resultsmentioning
confidence: 99%
“…18,[22][23][24][25][26][27][28][29][30][31][32]48 Three articles evaluating the outcomes of pharmacist prescribing on the use of antihypertensives, 24 cardiovascular risk reduction 28 and health care use 23 were on study design and did not report any results. All remaining studies reported benefits of pharmacist prescribing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation